"Many of Us Have Been Previously Evicted": Exploring the Relationship Between Homelessness and Evictions Among Families Participating in the Rapid Rehousing Program in Salt Lake County, Utah. Issue 3 (3rd September 2021) - García, Ivis; Kim, Keuntae
ABSTRACT: This study is concerned with homeless families that returned to the shelter and qualified to participate in the Rapid Rehousing Program (RRHP) again. Because RRH is a short-term voucher where families rent in the private market, one of the main barriers to finding housing is having an eviction record. Focus groups with tenants and case managers/service providers, as well as interviews with landlords participating in The Road Home's RRHP in Salt Lake County, found that families tend to find housing in buildings where other homeless families with multiple evictions and criminal records are concentrated. Tenants often encounter lenient landlords, only to be evicted at a later time. Families returned to the shelter for various reasons, but mainly because after their RRH voucher ends, households end up violating their leases due to nonpayment. The article offers recommendations to those administering RRHP about how evictions and becoming homeless again can be prevented.